Pengaruh beban lampu terhadap tegangan, arus, dan rpm pada turbin angin savonius 2 sudu - Ahmadi, Ahmadi; Irfa`i, Mochamad Arif; Basuki, Basuki (Universitas Muhammadiyah Metro, 2020)
Right now using of electrical energy in society is increasing. This is reason in doing the work, peoples using tools machine that required voltage source as driver. The explanation to be basic for research about convertion of wind energy to electrical with making vertical axis wind turbine. The aim is find out effect of lamp load to voltage, current, and RPM on the 2 blade savonius wind turbine. This is a experiment research. This research using quantitative descriptive analysis, with independent variables are lamp load 0, 3, 6, 9 watts and the dependent variables are voltage, current, and RPM. Results obtain from testing then analysis and conclusion attract. Results research show highest performance of savonius 2 blades wind turbine on 0 watt lamp load it producting, 11.68 volts, 0 ampere, and 334.2 RPM. Lowest performance of 2 blades savonius wind turbine on 9 watt lamp load producting, 7.68 volts, 0.13 amperes, and 272.9 RPM. Based of results on the test can concluded that, The more lamp loads activated, voltage and RPM values decrease while, current value increases. This is because number of lamp loads increas then, amount electric charge moving per unit of time also increas.